Running Mac OS X Tiger - Davidson, James Duncan (O'Reilly, 2005)
Running Mac OS X Tiger is the ideal resource for power users and system administrators like you who want to tweak Tiger, the new release of Mac OS X, to run faster, better, or just differently. If you areready to dig deep into your Mac, this book expertly guides you to the core of Mac OS X. It helps you understand the inner workings of the operating system so you can know how to get the most out of it. And it gives you countless ideas--and step-by-step instruction--for customizing and revving up Tiger to your specific needs and your liking. Completely revised and updated for Mac OS X Tiger, Running Mac OS X Tiger covers all the new features and functionality of Tiger. You can count on authors Jason Deraleau and James Duncan Davidson to give what you need--and not bother with what you don't. They don't spend time on Finder tips and keyboard shortcuts; they focus on showing you what makes a Mac tick and, more importantly, how you can make it tick just the way you want it to. Easy to follow and intuitively organized, Running Mac OS X Tiger is divided into three parts: "Getting Started" introduces Mac OS X and explains how it's put together and why it works; "Administration Essentials" gives you the tools you need to examine how your system is running and adjust all the knobs behind its operation; and "Networking and Network Services" covers the ways Mac OS X interfaces with the world around it, including wireless and spontaneous networking. Developer Tools for Mac OS X, including Xcode, are discussed throughout the book as appropriate. For the growing number of intermediate to advanced users who are ready and eager to customize Mac OS X, Running Mac OS X Tiger delivers everything you need to become master of your Mac.